2021
DOI: 10.1101/2021.06.06.21258414
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of immunosuppressive therapy reduction and early post-infection graft function in kidney transplant recipients with COVID-19

Abstract: Kidney transplant (KT) recipients with COVID-19 are at high risk of poor outcomes because of comorbidities and long-term immunosuppressive therapy (IST). There are little data on the effect of IST reduction and early graft function after COVID-19. We conducted a retrospective study on 45 consecutive KT recipients followed at the University Hospital of Modena who tested positive for COVID-19 by RT-PCR analysis. We detailed clinical management and outcomes of these patients. Median age of patients was 56.1 (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(32 reference statements)
1
1
0
Order By: Relevance
“…Interestingly, we observed an improvement in AF 1 month after treatment for severe COVID-19 compared with that before infection. This phenomenon was also reported in a study from Italy, in which hospitalized KTRs had better AF after discharge than before infection, with no difference in non-hospitalized KTRs ( 28 ). However, this study did not specify whether the phenomenon occurred in patients with non-severe or severe COVID-19.…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, we observed an improvement in AF 1 month after treatment for severe COVID-19 compared with that before infection. This phenomenon was also reported in a study from Italy, in which hospitalized KTRs had better AF after discharge than before infection, with no difference in non-hospitalized KTRs ( 28 ). However, this study did not specify whether the phenomenon occurred in patients with non-severe or severe COVID-19.…”
Section: Discussionsupporting
confidence: 78%
“…Other reasons for the deterioration in blood pressure regulation in our patients may be the discontinuation of RAS blocker drugs in the early stages of the epidemic, with the belief that ACEi or ARB drugs adversely affect the course of the disease or the fact that the virus may change the homeostasis of the renin-angiotensin-aldosterone system (RAAS) with the ACE2 interaction. 43 Longer transplantation time is associated with higher mortality and more frequent AKI during COVID-19. 5 We found that patients with a long transplantation period have more proteinuria after COVID-19.…”
Section: Discussionmentioning
confidence: 99%